Analisis Penggunaan Media Digital Kahoot: Numbers By Dragon Box Pada Pembelajaran Matematika Dalam Melatih Anak Berfikir Kritis - M Iqbal Arrosyad; Fanika Yuliana; Siti Nurjannah; Marina Marina (CV. Alim's Publishing, 2023)
The purpose of this study is to review more deeply the use of digital media kahoot: by dragon box in learning mathematics accompanied by a description of the obstacles experienced during the use of digital-based learning media: kahoot number by dragon box in learning mathematics in training children to think critically. Qualitative description methods with interview techniques and the application of digital media include participatory observation, interviews, and documentation. The subjects of this study were students aged 6-9 years from Kindergarten to Grade 3 Elementary School. The results of this study indicated that the implementation of digital teaching media was carried out in four stages, namely the action planning stage to develop a plan for using digital teaching media that is suitable for use in learning mathematics in training children to think critically, the stage of carrying out the action by learning mathematics material using digital media through the educational game kahoot: numbers by dragon box, the stage of the action results as an effort to successfully use digital teaching media that is good for the development of children's thinking from the beginning to the end of use, and the stage of reflection by assessing how the process implementation and results in the use of digital teaching media for children aged 6-9 years. And the obstacles found in the use of digital teaching media are in the form of installing applications and registering accounts, the process of carrying out digital teaching media.